Mainstreaming Genetic Testing for Adult Patients With Autosomal Dominant Polycystic Kidney Disease. (October 2021) - Elliott, Mark D.; James, Leslie C.; Simms, Emily L.; Sharma, Priyana; Girard, Louis P.; Cheema, Kim; Elliott, Meghan J.; Lauzon, Julie L.; Chun, Justin
Purpose: Genetic testing results are currently obtained approximately 1 year after referral to a medical genetics team for autosomal dominant polycystic kidney disease (ADPKD). We evaluated a mainstream genetic testing (MGT) pathway whereby the nephrology team provided pre-test counseling and selection of patients with suspected ADPKD for genetic testing prior to direct patient interaction by a medical geneticist. Sources of information: A multidisciplinary team of nephrologists, genetic counselors, and medical geneticists developed an MGT pathway for ADPKD using current testing criteria for adult patient with suspected ADPKD and literature from MGT in oncology. Methods: An MGT pathway was assessed using a prospective cohort and compared to a retrospective cohort of 56 patients with ADPKD who received genetic testing using the standard, traditional pathway prior to implementing the MGT for ADPKD. The mainstream pathway was evaluated using time to diagnosis, diagnostic yield, and a patient survey to assess patient perceptions of the MGT pathway. Key findings: We assessed 26 patients with ADPKD using the MGT and 18 underwent genetic testing with return of results. Of them, 52 patients had data available for analysis in the traditional control cohort. The time for return of results using our MGT pathway was significantly shorter with a median time to results of 6 months compared to 12 months for the traditional pathway. We identified causative variants in 61% of patients, variants of uncertain significance in 28%, and 10% had negative testing which is in line with expectations from the literature. The patient surveys showed high satisfaction rates with the MGT pathway. Limitations: This report is an evaluation of a new genetic testing pathway restricted to a single, publicly funded health care center. The MGT pathway involved a prospective collection of a limited number of patients with ADPKD with comparison to a retrospective cohort of patients with ADPKD evaluated by standard testing. Implications: A MGT pathway using clearly defined criteria and commercially available gene panels for ADPKD can be successfully implemented in a publicly funded health care system to reduce the time required to obtain genetic results.